Characterization of solar photovoltaic modules powered by artificial light for use as a source for smart sensors - Ghislain Mengounou Mengata; Steve Ngoffe Perabi; Francelin Edgar Ndi; Yufenyuy Severine Wiysahnyuy (Energy Reports, 2022)
Making the environment “smart” requires intelligent sensors which must be equipped with self-power supply systems that are sustainable and environmentally friendly but presents low maintenance cost. Photovoltaic modules demonstrate a remarkable energy harvesting technology that can meet up to most of the requirements of these sensors. Inside buildings, natural solar light is not available therefore if PV modules are used in buildings, they must function with artificial light. This piece of work consists of investigating the performances of available PV modules under artificial light sources. Four PV modules based on the monocrystalline; m-Si and polycrystalline; p-Si technologies (m-Si PV1, p-Si PV2, p-Si PV3 and m-Si PV4) are measured under four artificial light sources and at varying illumination levels from 100 lx to 2000 lx. The representation and analysis of the characteristics show that best performances were recorded for the module m-Si PV4 reaching power densities of up to 555.83 μW/cm2, 382.96 μW/cm2 and 1065.69μW/cm2 at 2000 lx under the incandescent lamp, lamp combination (LED, CFL, and Incandescent) and the halogen lamp respectively. On the other hand, worst performances of modules were observed under the LED lamp and the CFL with power densities ranging from only 0.16μW/cm2 at 100 lx recorded for p-Si PV3 to 23.63μW/cm 2 at 2000 lx recorded for m-Si PV4 and 0.22μW/cm 2 at 100 lx for p-Si PV3 to 27.37μW/cm2 at 2000 lx recorded for m-Si PV4 respectively for the LED lamp and CFL. The m-Si based PV modules therefore perform better than the p-Si based modules under artificial light.